Tingkat Prokrastinasi Akademik Pada Siswa SMP - Kuswidyawati, Dheanita; Setyandari, Anastasia (Universitas Sanata Dharma, 2023)
This research is a descriptive quantitative research which aims to: 1) Describe the level of academic procrastination in students of SMP Negeri 3 Yogyakarta for the 2021/2022 academic year. 2) Knowing the items in the academic procrastination questionnaire that are identified as high to be proposed as tutoring topics. The subjects in this study were 123 class VII students of SMP Negeri 3 Yogyakarta for the academic year 2021/2022. The data collection in this study used a survey method by filling out a questionnaire of 39 valid items out of 50 items that had been made previously and had a Cronbach Alpha reliability index of 0.877. The scale is arranged based on aspects of academic procrastination, namely: (1) there are delays in starting or completing work on the task at hand. , (2) slowness in carrying out tasks, (3) time gap between plans and actual performance, (4) doing other activities that are more enjoyable than doing the tasks that must be done. The results of the study show that (1) the level of academic procrastination carried out by students of SMP Negeri 3 Yogyakarta for the 2021/2022 academic year tends to be at a moderate level, in more detail, including 4.87% in the high category, 60.97% in the medium category, 29.26 % in the low category, and 4.87% in the very low category. (2) the results of item analysis showed 4 items (10%) identified as high, in the medium category there were 17 items (44%), 18 items (46%) in the low category. Based on the items in the high and medium categories, it can be proposed as personal study guidance topics. The proposed guidance topic concerns all aspects of procrastination.